Enhancement of the power factor in two‐phase silicon–boron nanocrystalline alloys. Issue 6 (9th April 2014) - Narducci, Dario; Lorenzi, Bruno; Zianni, Xanthippe; Neophytou, Neophytos; Frabboni, Stefano; Gazzadi, Gian Carlo; Roncaglia, Alberto; Suriano, Francesco
<x xml:space="preserve">Abstract</x> In previous publications it was shown that the precipitation of silicon boride around grain boundaries may lead to an increase of the power factor in nanocrystalline silicon. Such an effect was further explained by computational analyses showing that the formation of an interphase at the grain boundaries along with high boron densities can actually lead to a concurrent increase of the electrical conductivity σ and of the Seebeck coefficient S. In this communication we report recent evidence of the key elements ruling such an unexpected effect. Nanocrystalline silicon films deposited onto a variety of substrates were doped to nominal boron densities in excess of 1020 cm−3 and were annealed up to 1000 °C to promote boride precipitation. Thermoelectric properties were measured and compared with their microstructure. A concurrent increase of σ and S with the carrier density was found only upon formation of an interphase. Its dependency on the film microstructure and on the deposition and processing conditions will be discussed.